The uncommon appeal of clouds [compact disc, unabridged] - McCall Smith, Alexander, 1948- (McCall Smith, Alexander, 1948- Isabel Dalhousie series., 2012)
Edinburgh philosopher and amateur sleuth Isabel Dalhousie finds herself tested as a parent, philosopher, sleuth, and friend in the ninth book of her mystery series. When a wealthy art collector seeks her help when a valuable painting is stolen from him, she discovers that the thieves are closer to the owner than he would have expected. At the same time, Isabel must decide what to do with her son when she discovers he's a budding mathematical genius.